159k views
0 votes
Let a1, a2, . . . , ak be integers with gcd(a1, a2, . . . , ak) = 1, i.e., the largest positive integer dividing all of a1, . . . , ak is 1. Prove that the equation a1u1 + a2u2 + · · · + akuk = 1

1 Answer

2 votes

Answer:

Solve by mathematical induction.

Explanation:

Let
a_1,a_2, \ldots, a_k be integers with
GCD(a_1,a_2, \ldots ,a_k) = 1.

We need to prove that


a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1

has a solution in integers
u_1,u_2, \ldots, u_k \in \mathbb{Z}.

To do so, we will use mathematical induction.

The base case

Consider the case for
n=2. Then,


GCD(a_1,a_2) = 1

and we need to prove that


a_1u_1 + a_2u_2 = 1.

Since the largest positive integer dividing
a_1 and
a_2 is 1, by the Euclidean algorithm, we have


\left( \exist u_1, u_2 \in \mathbb{Z}\right) a_1u_1 + a_2u_2 = 1

Therefore, the statement is true for
n=2.

The induction step

This step proves that if the property holds for one natural number
n, then it holds for the next natural number
n+1. Combined wit the base case, it will establish the property for
\forall n \in \mathbb{N}.

Now, suppose that the statement is true for
n=k.

This means that


GCD(a_1, a_2, \ldots, a_k) = 1 \implies \left( \exists u_1, u_2, \ldots u_k \in \mathbb{Z}\right) a_1u_1 + a_2u_2 +\ldots+ a_ku_k = 1

Let's check if the statement holds true for the next natural number, that is
n= k+1.


GCD(a_1, a_2, \ldots, a_(k+1)) = 1 \implies GCD(a_1, a_2, \ldots, a_k) = 1 \: \wedge \: GCD(a_k, a_(k+1)) = 1

By the Euclidean algorithm, we have


GCD(a_1, a_2, \ldots, a_(k)) = 1 \implies \left(\exists u_1,u_2, \ldots, u_k \in \mathbb{Z}\right)a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1

and


GCD(a_k, a_(k+1)) = 1 \implies \left(\exists u_1,u_2, \in \mathbb{Z}\right)a_ku_k + a_(k+1)u_(k+1) = 1

Now, multiply the obtained equations.


(a_1u_1 + a_2u_2 + \ldots + a_ku_k)(a_ku_k + a_(k+1)u_(k+1)) = 1 \cdot 1

Removing parenthesis gives


a_1u_1 \cdot a_ku_k + a_2u_2\cdot a_ku_k + \ldots + a_ku_k \cdot a_ku_k +\\a_1u_1 \cdot a_(k+1)u_(k+1) + a_2u_2\cdot a_(k+1)u_(k+1) + \ldots + a_ku_k \cdot a_(k+1)u_(k+1) =1

Now, collect up the terms by
a_1, a_2, \ldots, a_(k+1).


a_1\underbrace{(u_1 a_ku_k +u_1 \cdot a_(k+1)u_(k+1))}_{\in \mathbb{Z}}+ a_2\underbrace{(u_2 a_ku_k+ u_2 a_(k+1)u_(k+1) )}_{\in \mathbb{Z}} + \ldots + a_(k+1)\underbrace{(a_ku_k u_(k+1))}_{\in \mathbb{Z}} \\ =1

Now, denote


u'_1 =u_1 a_ku_k +u_1 \cdot a_(k+1)u_(k+1),u'_2=u_2 a_ku_k+ u_2 a_(k+1)u_(k+1), \ldots, u'_(k+1) =a_ku_ku_(k+1)

Therefore,


\left(\exists u'_1,u'_2, \ldots, u'_(k+1) \in \mathbb{Z}\right)a_1u'_1 + a_2u'_2 + \ldots + a_(k+1)u'_(k+1) = 1

Hence, the equation


a_1u_1 + a_2u_2 + \ldots + a_ku_k = 1

has a solution in integers
u_1,u_2, \ldots, u_k \in \mathbb{Z}.

User Griv
by
5.2k points